Cultural globalization and its profound effect on the English language proliferation - Grechykhina, N.; Гречихіна, Н. (КНТУ, 2013)
In this article the proliferation of English language under the impact of cultural globalization and its effect on the society is considered. В статті розглядається розповсюдження англійської мови під діянням культурних глобалізаційних процесів та їх вплив на суспільне життя.
Культурна глобалізація та її значний вплив на розповсюдження англійської мови
Keywords: integration; globalization; denominator; proliferation; globalized power relations; multilingual; cultural globalization